Clinical Profile of Ischemic Stroke in Type 2 Diabetic Patients: Experience in a Tertiary Care Hospital (BIRDEM Medical Journal, 2016)
Background: Stroke is the third highest cause of morbidity and mortality in the world. Diabetes mellitus increases risk of ischemic stroke. Stroke in diabetic patients is different from stroke in non-diabetics in several perspectives. This cross-sectional study was carried out to observe clinical profile of ischemic stroke in Type 2 diabetic patients.Materials and Methods: This cross-sectional observational study was done in the Department of Neurology, BIRDEM General Hospital from April to September, 2010. Non-probability purposive sampling was used.Results: A total number of 50 subjects were included, all were hospitalized ischemic stroke with type- 2 diabetic patient. Maximum number (36.0%) of the patients was in between 61 to 70 years age group with mean age 59.9 ±13.9 years. There was male predominance and male-female ratio was1.5: 1. Majority of the patient (50%) noticed features of stroke at morning (6 am-12.00 noon).Regarding risk factor profile, 35(70%) had uncontrolled DM, 35(70%) used to lead sedentary lifestyle, 30(60%) had history of tobacco use, 20(40%) had Obesity and 42(84%) were hypertensive. A Few cases 5 (10%) were alcoholic. Most (90%) of the patients admitted with weakness at either half of body. Some had difficulties in speech (80%), altered consciousness (24%), difficulties in swallowing (4%); rest of the patients had facial weakness (4%) and others (2%). 94.0% patient had regular pulse, 6% had irregular pulse. 80.0% had high blood pressure on admission. Mean systolic and diastolic blood pressure was 153± 5.3 mm of Hg and 97±4.4 mm of Hg respectively. 40.0% patient had abnormal fundoscopy (Diabetic and/or hypertensive retinopathy). Carotid bruit was found in 2% case but one had sign of dyslipidaemia. 76% was conscious and oriented, 24%altered conscious level, 90% had hemiplegia or hemiparesis, 72% had dysarthria, 4% had dysphasia and 16% others.Conclusion: Elderly and male people are more prone to develop ischemic stroke. Hemiparesis or hemiplegia, dysarthria is the major clinical presentation and high blood pressure is an important risk factor for ischemic stroke. Further study can be done to compare the clinical profile between diabetic and non-diabetic populations.Birdem Med J 2015; 5(2): 88-91